Multi-generational exposure to Pb in two monophyletic Daphnia species: Individual, functional and population related endpoints - Araujo, G. S.; Abessa, D. M. S. [UNESP]; Soares, A. M. V. M.; Loureiro, S. (Elsevier B.V., 2019)
To better evaluate chemical damage in chronically contaminated habitats, a nine-generational exposure to Lead (Pb) was done with two monophyletic Daphnia species, from temperate (Daphnia magna) and tropical (Daphnia similis) environments. The multi-generational test consisted generally of a continuous Pb exposed set of organisms, plus an extra control set running simultaneously. To assess daphnids recovery after Pb exposure, some organisms from the sixth generation were transferred to clean media for three extra generations (recovery period; F6 to F9), while others were keep Pb exposed. All setups (control, Pb exposure and recovery period) were submitted to two different dietary regimes, the standard (3 x 10(5) cells/mL) and restricted food (1.5 x 10(5) cells/mL) regimes. To evaluate the effects of generational Pb exposure and food regimes, individual, functional and population related endpoints were assessed (number of offspring, body length and rate of population increase (r) and feeding rate (FR)). The tests were conducted on the first (F0) and last generations (F9). No differences were shown on number of offspring and feeding among F9 control and continuous Pb exposed D. magna, although a higher r was shown for F9 Pb exposed organisms. F9 Pb exposed D. similis also presented a higher r than F9 control, however, lethality was induced at high Pb exposure levels. At food restriction the patterns were opposite and D. magna died at high Pb exposure while Pb exposed D. similis was the only setup (compared to control and recovery period) to survive at high Pb exposure levels. Regarding the recovery period, D. magna (standard food) did not cope well with the Pb re-exposure and lethality was induced, while D. similis indicate a decreased Pb sensitivity (only setup that survived high Pb exposure levels). Under food restriction, both species presented a decreased Pb sensitivity and consequent failed recovery (possibly due to epigenetic changes). Both species presented similar patterns regarding generations. Organisms from F0 presented enhanced reproductive outputs in comparison to F9 and the contrary occurred to the FR (even in control organisms). Data show an acclimation under a generational Pb exposure, which could increase the population of adapted organisms in natural habitats. And, since there was not a full recovery after three generations in clean media, an indication of epigenetic changes for both species may also be considered.
Keywords: Multi-generation; Daphnids; Lead; Reproduction endpoints; Feeding rate